TRANSPARANSI PENGELOLAAN DANA DESA: EVALUASI KEBIJAKAN DAN IMPLEMENTASI - Wulandari, Wulandari; Al-Amin (CV. Adiba Aisha Amira, 2025)
This study aims to evaluate the policy and implementation of transparency in village fund management in Indonesia through a literature review method. Transparency in village fund management is crucial to ensure effective use of funds, prevent misuse, and enhance public trust in village governments. The results of the study indicate that transparency policies have been clearly regulated through regulations such as the Village Law and Permendagri No. 20 of 2018, and supported by innovative systems such as Siskeudes, which facilitates reporting and access to village financial information. However, implementation at the village level still faces various obstacles, including limited human resources, technological infrastructure, and low community literacy. Therefore, strengthening the capacity of village officials, optimising the use of technology, and increasing community participation are key factors in achieving transparent, accountable, and sustainable village fund management.